Inflammatory bowel disease does not alter the clinical features and the management of acute pancreatitis: A prospective, multicentre, exact-matched cohort analysis - İNCE, ALİ TÜZÜN; Dohos, Dóra; Farkas, Nelli; Váradi, Alex; Erőss, Bálint; Párniczky, Andrea; Szentesi, Andrea; Hegyi, Péter; Sarlós, Patrícia; Czakó, László; Boros, Eszter; Hussein, Tamás; et al. (My University, 2022)
© 2022 The AuthorsObjective and aims: Acute pancreatitis in inflammatory bowel disease occurs mainly as an extraintestinal manifestation or a side effect of medications. We aimed to investigate the prognostic factors and severity indicators of acute pancreatitis and the treatment of patients with both diseases. Design: We performed a matched case-control registry analysis of a multicentre, prospective, international acute pancreatitis registry. Patients with both diseases were matched to patients with acute pancreatitis only in a 1:3 ratio by age and gender. Subgroup analyses were also carried out based on disease type, activity, and treatment of inflammatory bowel disease. Results: No difference in prognostic factors (laboratory parameters, bedside index of severity in acute pancreatitis, imaging results) and outcomes of acute pancreatitis (length of hospitalization, severity, and local or systemic complications) were detected between groups. Significantly lower analgesic use was observed in the inflammatory bowel disease population. Antibiotic use during acute pancreatitis was significantly more common in the immunosuppressed group than in the non-immunosuppressed group (p = 0.017). However, none of the prognostic parameters or the severity indicators showed a significant difference between any subgroup of patients with inflammatory bowel disease. Conclusion: No significant differences in the prognosis and severity of acute pancreatitis could be detected between patients with both diseases and with pancreatitis only. The need for different acute pancreatitis management is not justified in the coexistence of inflammatory bowel disease, and antibiotic overuse should be avoided.